Low-Voltage Electrical Installations : (IEC, 2009)
The particular requirements as specified in this part of IEC 60364 are applicable to mobile or transportable units. For the purposes of this part, the term " unit" refers to a vehicle and/or mobile or transportable structure in which all or part of an electrical installation is contained. Units are either of the mobile type or of the transportable type